2014
DOI: 10.1371/journal.pone.0089868
|View full text |Cite|
|
Sign up to set email alerts
|

Demographic and Clinico-Epidemiological Features of Dengue Fever in Faisalabad, Pakistan

Abstract: This cross-sectional study was carried out to explore the epidemiological and clinical features of dengue fever in Faisalabad, Pakistan during 2011 and 2012. During the study period, anti-dengue IgM positive cases were reported in the post-monsoon period during the months of August–December. Certain hotspots for the dengue infection were identified in the city that coincide with the clusters of densely populated urban regions of the city. Out of total 299 IgM positive patients (male 218 and female 81); there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 25 publications
7
31
2
Order By: Relevance
“…These findings are inconsistent with three studies performed in Australia, France and Mexico, which documented that DF was more common among the female population. However, they did not find statistically significant relationships [23,25,26].…”
Section: Discussionmentioning
confidence: 83%
“…These findings are inconsistent with three studies performed in Australia, France and Mexico, which documented that DF was more common among the female population. However, they did not find statistically significant relationships [23,25,26].…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, the flood of 2012 started in early September, and like the previous one, it was also the result of heavy monsoon rains in KPK, Upper Sindh, Balochistan, and http://en.wikipedia.org/wiki/South_Punjab http://en.wikipedia.org/wiki/Punjab_(Pakistani_province). This resulted in the spread of infectious diseases such as bacterial and vector‐borne infections, including dengue …”
Section: Factors Influencing Disease Spreadmentioning
confidence: 89%
“…Dengue is also considered a water‐borne disease, as mosquitoes typically flourish in aquatic habitats, where they lay eggs in water‐filled containers. Thus, epidemics of DF tend to occur annually during rainy seasons in the tropics and interannually after weather events with a more hot and humid environment enhanced by electricity crisis in countries like Pakistan . Moreover, mosquitoes also flourish in hot and dry conditions because natural predators of mosquitoes are greatly reduced during drought times, as wetlands dry up …”
Section: Factors Influencing Disease Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we did not find statistically significant association of splenomegaly with severe illness. In a recently published report from Pakistan, it was observed that significant number of patients with severe dengue had splenomegaly [22]. The reason for spleen enlargement in severe dengue infection may be due to replication of dengue virus in spleen, resulting in splenomegaly [23].…”
Section: Pereira Et Almentioning
confidence: 99%